Answer:
The <em>equation</em> of the tangent line is given by the following equation:
![\displaystyle y - \frac{1}{e} = \frac{-1}{e} \bigg( x - 1 \bigg)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20-%20%5Cfrac%7B1%7D%7Be%7D%20%3D%20%5Cfrac%7B-1%7D%7Be%7D%20%5Cbigg%28%20x%20-%201%20%5Cbigg%29)
General Formulas and Concepts:
<u>Algebra I</u>
Point-Slope Form: y - y₁ = m(x - x₁)
- x₁ - x coordinate
- y₁ - y coordinate
- m - slope
<u>Calculus</u>
Differentiation
- Derivatives
- Derivative Notation
Derivative Property [Multiplied Constant]:
![\displaystyle \frac{d}{dx} [cf(x)] = c \cdot f'(x)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bd%7D%7Bdx%7D%20%5Bcf%28x%29%5D%20%3D%20c%20%5Ccdot%20f%27%28x%29)
Derivative Rule [Basic Power Rule]:
- f(x) = cxⁿ
- f’(x) = c·nxⁿ⁻¹
Derivative Rule [Chain Rule]:
![\displaystyle \frac{d}{dx}[f(g(x))] =f'(g(x)) \cdot g'(x)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%28g%28x%29%29%5D%20%3Df%27%28g%28x%29%29%20%5Ccdot%20g%27%28x%29)
Step-by-step explanation:
*Note:
Recall that the definition of the derivative is the <em>slope of the tangent line</em>.
<u>Step 1: Define</u>
<em>Identify given.</em>
<em />![\displaystylef(x) = e^{-x} \\x = -1](https://tex.z-dn.net/?f=%5Cdisplaystylef%28x%29%20%3D%20e%5E%7B-x%7D%20%5C%5Cx%20%3D%20-1)
<u>Step 2: Differentiate</u>
- [Function] Apply Exponential Differentiation [Derivative Rule - Chain Rule]:
![\displaystyle f'(x) = e^{-x}(-x)'](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20e%5E%7B-x%7D%28-x%29%27)
- [Derivative] Rewrite [Derivative Rule - Multiplied Constant]:
![\displaystyle f'(x) = -e^{-x}(x)'](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20-e%5E%7B-x%7D%28x%29%27)
- [Derivative] Apply Derivative Rule [Derivative Rule - Basic Power Rule]:
![\displaystyle f'(x) = -e^{-x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%28x%29%20%3D%20-e%5E%7B-x%7D)
<u>Step 3: Find Tangent Slope</u>
- [Derivative] Substitute in <em>x</em> = 1:
![\displaystyle f'(1) = -e^{-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%281%29%20%3D%20-e%5E%7B-1%7D)
- Rewrite:
![\displaystyle f'(1) = \frac{-1}{e}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%27%281%29%20%3D%20%5Cfrac%7B-1%7D%7Be%7D)
∴ the slope of the tangent line is equal to
.
<u>Step 4: Find Equation</u>
- [Function] Substitute in <em>x</em> = 1:
![\displaystyle f(1) = e^{-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%281%29%20%3D%20e%5E%7B-1%7D)
- Rewrite:
![\displaystyle f(1) = \frac{1}{e}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20f%281%29%20%3D%20%5Cfrac%7B1%7D%7Be%7D)
∴ our point is equal to
.
Substituting in our variables we found into the point-slope form general equation, we get our final answer of:
![\displaystyle \boxed{ y - \frac{1}{e} = \frac{-1}{e} \bigg( x - 1 \bigg) }](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cboxed%7B%20y%20-%20%5Cfrac%7B1%7D%7Be%7D%20%3D%20%5Cfrac%7B-1%7D%7Be%7D%20%5Cbigg%28%20x%20-%201%20%5Cbigg%29%20%7D)
∴ we have our final answer.
---
Learn more about derivatives: brainly.com/question/27163229
Learn more about calculus: brainly.com/question/23558817
---
Topic: AP Calculus AB/BC (Calculus I/I + II)
Unit: Differentiation